Linear systems with unstructured multiplicative uncertainty: Modeling and robust stability analysis - Matušů, Radek; Şenol, Bilal; Yeroğlu, Celaleddin (PLoS One, 2017)
This article deals with continuous-time Linear Time-Invariant (LTI) Single-Input Single-Output (SISO) systems affected by unstructured multiplicative uncertainty. More specifically, its aim is to present an approach to the construction of uncertain models based on the appropriate selection of a nominal system and a weight function and to apply the fundamentals of robust stability investigation for considered sort of systems. The initial theoretical parts are followed by three extensive illustrative examples in which the first order time-delay, second order and third order plants with parametric uncertainty are modeled as systems with unstructured multiplicative uncertainty and subsequently, the robust stability of selected feedback loops containing constructed models and chosen controllers is analyzed and obtained results are discussed.
Keywords: Programming, Linear; programování lineární; Uncertainty; nejistota